Long- and short-term acclimation of the photosynthetic apparatus to salinity in Chlamydomonas reinhardtii. The role of Stt7 protein kinase - Devadasu, Elsinraju; Kanna, Sai Divya; Neelam, Satyabala; Yadav, Ranay Mohan; Nama, Srilatha; Akhtar, Parveen; Polgár, Tamás F.; Ughy, Bettina; Garab, Győző; Lambrev, Petar H.; Subramanyam, Rajagopal (Frontiers in Plant Science, 2023)
Salt is a major stress factor to the growth of algae and plants. Here, our study mainly focuses on the organization of the photosynthetic apparatus to the long-term responses of NaCl in Chlamydomonas (C.) reinhardtii. We analyzed the physiological effects of salt treatment at a cellular, membrane, and protein level by microscopy, protein profile analyses, transcripts, circular dichroism spectroscopy, chlorophyll fluorescence transients, and steady-state and time-resolved fluorescence spectroscopy. We have ascertained that palmelloid formation of sphere-shaped colonies where daughter cells with curtailed flagella are enclosed within the mother cell walls in C. reinhardtii cells grown in a high salinity medium, depends on the presence of a cell wall, as suggested by cell wall-less mutant CC-503. Using the stt7 mutant cells, we show Stt7 kinase-dependent phosphorylation of light-harvesting complex II (LHCII) in both short- and long-term treatments of various NaCl concentrations – demonstrating NaCl-induced state transitions that are similar to light-induced state transitions. The grana thylakoids were less appressed (with higher repeat distances), and cells grown in 150 mM NaCl showed disordered structures that formed diffuse boundaries with the flanking stroma lamellae. PSII core proteins were more prone to damage than PSI. At high salt concentrations (100–150 mM), LHCII aggregates accumulated in the thylakoid membranes. Low-temperature and time-resolved fluorescence spectroscopy indicated that the stt7 mutant was more sensitive to salt stress, suggesting that LHCII phosphorylation has a role in the acclimation and protection of the photosynthetic apparatus.